'Celts: art and identity' exhibition: 'New Celticism' at the British Museum. (17th February 2016) - Fernández-Götz, Manuel
Abstract : Controversies about the 'Celts' have constituted an ongoing debate over the last few decades, with postures ranging from blank scepticism and denial, to critical revisions, but also to the maintenance of more traditional approaches. After a lively and overall useful debate in the pages of Antiquity between 1996–1998 (principally with articles by Vincent and Ruth Megaw vs Simon James and John Collis), Simon James's controversial volume The Atlantic Celts. Ancient people or modern invention? (1999 ) attracted considerable attention, both among scholars and the wider public, encouraging discussions about the relationship—if any—between modern Celtic identities and the ancient Celts. A major milestone was reached with the publication of John Collis's monograph The Celts. Origins, myths and inventions (2003), which is probably the best historiographical review about the construction of the concept and the different sources involved from Antiquity to modern times. One of his main points is that classical sources never referred to the presence of Celts on the British Isles and that the use of the term for the populations of ancient Britain was mainly an invention of the modern era (see also Morse2005, How the Celts came to Britain ). From a rather different perspective, new approaches based mostly on linguistics emphasise the crucial role of the Atlantic façade in the development of Celtic languages (Cunliffe & Koch2010 ).